2014
DOI: 10.3390/v6041861
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Anti-Influenza Activity of the Chinese Herbal Plant Paeonia lactiflora

Abstract: Bai Shao (BS, the root of Paeonia lactiflora Pall.), a common Chinese herb in many recipes used to treat viral infection and liver diseases, is recognized for its ability to nourish menstruation, its Yin convergence, and as an antiperspirant. However, the mechanism and components for its antiviral function remain to be elucidated. In this study, an ethanolic extract of BS was further partitioned into aqueous and organic parts (EAex) for in vitro functional study and in vivo efficacy testing. EAex exhibited an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 33 publications
0
16
0
4
Order By: Relevance
“…Natural products appear to be a major source of anti-influenza drug discovery and offer new prospects for influenza management [ 14 , 15 , 16 , 17 , 18 ]. Quercetin (3,3’,4’,5,7-pentahydroxyflavone) is one of the most ubiquitous flavonoids, and it is found in many Chinese herbs, vegetables and fruits, as well as red wine [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural products appear to be a major source of anti-influenza drug discovery and offer new prospects for influenza management [ 14 , 15 , 16 , 17 , 18 ]. Quercetin (3,3’,4’,5,7-pentahydroxyflavone) is one of the most ubiquitous flavonoids, and it is found in many Chinese herbs, vegetables and fruits, as well as red wine [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…C'est l'hémagglutinine qui permet l'attachement à la membrane cellulaire et la fusion avec la membrane de l'endosome libérant la capside dans le cytoplasme. Des études ont montré que des tanins issus de différentes plantes inhibent l'attachement et la pénétration du virus influenza A-H1N1 par agrégation de cette protéine [23,[35][36][37]. Les tanins présents dans l'extrait de cyprès pourraient donc avoir produit la perte du pouvoir infectieux du virus influenza A-H1N1 de la même manière, ainsi que celle des autres virus enveloppés qui comportent aussi des protéines d'enveloppe impliquées dans l'attachement et la pénétration.…”
Section: Activité Virucideunclassified
“…Chez l'animal et chez l'Homme, des effets bénéfiques de différents extraits de plantes ont été rapportés lors d'une infection par le virus influenza [27,35,37,[45][46][47][48][49][50]. Il serait donc intéressant d'évaluer aussi les effets de l'extrait de cyprès, seul et en association aux traitements conventionnels, chez l'Homme, ainsi qu'en utilisation prophylactique et thérapeutique complémentaire chez les bovins.…”
Section: Activité Virucideunclassified
“…Pharmacological studies of this genus have shown a variety of activities, including analgesic, sedative, anti-inflammatory, antimicrobial, antitumor, antiviral, cardiovascular protection activities and so on [2][3][4]. The pharmacological activities are primarily attributed to monoterpenes, which has a "cage-like" pinane skeleton.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the antiviral activity of some species of Paeonia has been explored. It has been reported that the extract of P. lactiflora possesses anti-influenza activity and has the potential for development as an anti-influenza agent [2]. In addition, literature also reported that P. lactiflora and P. suffruticosa both showed antiviral activities against respiratory syncytial virus (RSV) [21].…”
Section: Introductionmentioning
confidence: 99%